Adenosine triphosphate‐induced photoreceptor death and retinal remodeling in rats. Issue 13 (3rd April 2014) - Vessey, Kirstan A.; Greferath, Ursula; Aplin, Felix P.; Jobling, Andrew I.; Phipps, Joanna A.; Ho, Tracy; De Iongh, Robbert U.; Fletcher, Erica L.
ABSTRACT Many common causes of blindness involve the death of retinal photoreceptors, followed by progressive inner retinal cell remodeling. For an inducible model of retinal degeneration to be useful, it must recapitulate these changes. Intravitreal administration of adenosine triphosphate (ATP) has recently been found to induce acute photoreceptor death. The aim of this study was to characterize the chronic effects of ATP on retinal integrity. Five‐week‐old, dark agouti rats were administered 50 mM ATP into the vitreous of one eye and saline into the other. Vision was assessed using the electroretinogram and optokinetic response and retinal morphology investigated via histology. ATP caused significant loss of visual function within 1 day and loss of 50% of the photoreceptors within 1 week. At 3 months, 80% of photoreceptor nuclei were lost, and total photoreceptor loss occurred by 6 months. The degeneration and remodeling were similar to those found in heritable retinal dystrophies and age‐related macular degeneration and included inner retinal neuronal loss, migration, and formation of new synapses; Müller cell gliosis, migration, and scarring; blood vessel loss; and retinal pigment epithelium migration. In addition, extreme degeneration and remodeling events, such as neuronal and glial migration outside the neural retina and proliferative changes in glial cells, were observed. These extreme changes were also observed in the 2‐year‐old P23H rhodopsin transgenic rat model of retinitis pigmentosa. This ATP‐induced model of retinal degeneration may provide a valuable tool for developing pharmaceutical therapies or for testing electronic implants aimed at restoring vision. J. Comp. Neurol. 522:2928–2950, 2014. © 2014 Wiley Periodicals, Inc.